Single photon detection up to 2 µm in pair of parallel microstrips based on NbRe ultrathin films - C. Cirillo; M. Ejrnaes; P. Ercolano; C. Bruscino; A. Cassinese; D. Salvoni; C. Attanasio; G. P. Pepe; L. Parlato (Scientific Reports, 2024)
Abstract Superconducting microstrip single photon detectors (SMSPDs) are increasingly attracting the interest of the scientific community as a new platform for large area detectors with unprecedented advantaged in terms of fabrication. However, while their operativity at the telecommunication wavelength was achieved, working beyond 1.55 µm is challenging. Here, we experimentally demonstrate single-photon operation of NbRe microstrips at wavelengths of 1.55 and 2 µm. The devices are structured as pairs of parallel microstrips with widths ranging from 1.4 to 2.2 μm and lengths from 5 to 10 μm. This innovative design may assure large sensitive areas, without affecting the kinetic inductance, namely the time performance of the detectors. The results are discussed in the framework of the hot-spot two-temperature model.